2010
DOI: 10.1002/mabi.201000040
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of an Endosomolytic Polyamidoamine ISA23 with Vesicles Mimicking Intracellular Membranes: A SANS/EPR Study

Abstract: The mechanism of ISA23 · HCl interaction with model membrane vesicles (80-100 nm in diameter) was investigated using EPR in conjunction with SANS. For EPR, 16-DSE was dissolved in the vesicle membrane to measure its dynamics and polarity, whereas a spin-labeled (Tempo)-ISA 23 analogue was used to give a measure of the polymer flexibility. When ISA23 was added to the external vesicle surface, no interaction was found. This observation conflicts with the reported ability to lyse RBC, but is in agreement with rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…The results of the above papers on PAAs as protein carriers are in agreement with the previously mentioned results of basic research in the same field and, not unexpectedly, point to a similar conclusion. By a proper design of the acid/base properties and the hydrophobic/hydrophilic balance, there is little doubt that a number of PAAs may display intracellular protein transport ability.…”
Section: Biomedical and Biotechnological Applications Of Paassupporting
confidence: 89%
See 1 more Smart Citation
“…The results of the above papers on PAAs as protein carriers are in agreement with the previously mentioned results of basic research in the same field and, not unexpectedly, point to a similar conclusion. By a proper design of the acid/base properties and the hydrophobic/hydrophilic balance, there is little doubt that a number of PAAs may display intracellular protein transport ability.…”
Section: Biomedical and Biotechnological Applications Of Paassupporting
confidence: 89%
“…47) analogue was used to give a measure of the polymer flexibility. No interaction was found adding ISA23 to the external vesicle surface . This observation conflicts with the reported ability of ISA23 to lyse the membrane of red blood cells (RBC) at pH ≤ 5, but is in agreement with previous studies showing no effect on membrane permeability when this PAA was added to an incubation medium containing isolated lysosomal vesicles, whereas destabilized the lysosomal membrane if internalized into the lysosomal compartment .…”
Section: Biomedical and Biotechnological Applications Of Paassupporting
confidence: 71%
“…It has been shown that, during endocytosis and endosomal maturation, there is a gradual change in the pH from 6.0–6.2 in early endosome to 5.5 in late endosome to 4.5–5 in lysosome . Thus, developing polymeric systems that can rapidly degrade in a controlled way could possibly disrupt the endosome due to osmotic imbalance and help endosomal escape and cytosolic delivery of therapeutic agents. Thus, we investigated the degradation of pPKHE polymers in cells using fluorescent derivatives. The cellular uptake and subsequent trafficking of fluorescent-labeled polymers were examined using confocal microscopy at various time intervals.…”
Section: Resultsmentioning
confidence: 99%
“…But at pH 7.4, the deprotonated carboxyl group hindered the interaction between the polymer and anionic membrane. This was partly due to the polymer's tightly coiled conformation and more significantly, due to the repulsion like negative charges at polymer/membrane interface . As a result, ISA23 was nonhemolytic, and when injected, exhibited “stealthlike” properties and circulated for a long time in the blood stream without being recognized by the liver.…”
Section: Effects Of Various Functional Groups On Properties Of Poly(amentioning
confidence: 99%